PENYULUHAN PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) PADA KAUM IBU JEMAAT DORA INO TOBELO - Ariance Kastanja; Zeth Patty (HIRONO : Jurnal Pengabdian Masyarakat, 2026)
Family Medicinal Plants (TOGA) are a "living pharmacy" essential for independent family health to treat minor illnesses naturally and economically. However, its utilization in the community, especially in the partner groups, is often not optimal due to the perception that TOGA is merely an ornamental plant and a lack of technical knowledge regarding its cultivation and processing. This Community Service (PkM) activity aimed to empower the Kaum Ibu (Women's Group) of the Dora Ino Congregation in Wari Ino Village, Tobelo, in optimizing home yards through the development of various types of medicinal plants. The methods used included coordination, interactive counseling using powerpoint and leaflets, and technical cultivation demonstrations covering planting media processing and seedling techniques. A total of 20 participants were involved in the activity held in March 2026. Evaluation results showed a comprehensive increase in the participants' knowledge and skills regarding the curative and preventive functions of TOGA, as well as mastery of various planting models, both in open land and using limited containers such as polybags and recycled items. It is concluded that this activity successfully built natural family health independence while providing aesthetic value and economic potential for the congregation's environment.